Government Communication on Instagram as a Diffusion Channel: Public Engagement and Electric Bus Policy in Yogyakarta - Athar, Aditya Zharfan; Wardhana, Ardiyanto (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2026)
This study examines how government communication on Instagram functions as a diffusion channel in fostering public engagement and discursive adoption of a policy-driven innovation, focusing on the EV Trans Jogja electric bus program in Yogyakarta, Indonesia. Diffusion of innovations theory assumes a progression from awareness to adoption; however, empirical evidence remains limited regarding how this process unfolds when sustainability policies are communicated through government-managed social media. Existing studies on government Instagram use largely emphasize information dissemination and visibility, leaving diffusion dynamics across adoption stages underexplored. A qualitative case study design was employed by analyzing communication related to EV Trans Jogja published on the official @dishubdiy Instagram account between January and May 2025. Data consist of Instagram posts, captions, audience comment threads, and reply or non-reply practices, complemented by in-depth interviews and field observations. Guided by diffusion of innovations theory, the stages of knowledge, persuasion, decision, implementation, and confirmation were operationalized as analytical categories to identify discursive indicators of engagement and adoption. The findings indicate that Instagram communication effectively enhances public visibility and awareness of the electric bus program, demonstrating strong diffusion performance at the knowledge stage. However, communicative support declines at subsequent stages. Persuasion remains largely symbolic and weakly dialogic, decision-making is constrained by fragmented procedural information, and implementation and confirmation receive limited institutional reinforcement. Later-stage diffusion indicators are predominantly articulated through audience-generated discourse. These patterns reflect an institutional communication logic that prioritizes informational visibility over engagement-oriented interaction, thereby constraining diffusion beyond awareness. The study concludes that in government-led sustainability policies, social media visibility alone is insufficient to advance diffusion toward adoption. Effective diffusion requires interactive, audience-centered, and stage-specific communication strategies aligned with the informational and experiential needs of each diffusion stage.